Narratives of Compulsory Heterosexuality Struggles of Filipino Lesbians in the Selected Poems from Tingle: Anthology of Pinay Lesbian Writings - Barrera, Kenneth Ian (RIRAI Publisher, 2024)
Utilizing Adrienne Rich's concept of compulsory heterosexuality, this research investigates narratives and struggles of Filipina lesbians as depicted in selected poems from